(untitled) (Balneo and PRM Research Journal, 2024)
Background: Muscle Power (often expressed in terms of explosive strength or explosive force) is required in most sports activities that involve intense and rapid contractions. Purpose: Identifying the differences and their significance, between the muscle strength values for the female students of the Faculty of Physical Education and Sports, according to their classification by BMI levels. Material and method: 77 female students of the Faculty of Physical Education and Sport from Galati were evaluated through 6 upper body muscle power tests (30s Plyometric Push-Ups, Shot put, Medicine ball chest throw, Overhead Medicine Ball Throw-forward, Overhead, Medicine Ball Throw-backward, Overhand ball throw) and 7 lower body muscle power tests (Speed Test 10m, Standing Long Jump Test, Vertical Jump Test, 3-Hop Test, 30s Continuous vertical jumps, 30s Lateral double leg hop test, The multiple 5 bounds test). The groups were divided according to BMI levels (underweight 11 cases, normal weight 53 cases and overweight 13 cases). The non-parametric Kruskal–Wallis and Mann-Whitney U tests were used to assess the differences between groups. Results: Arithmetic average values indicate the superiority of underweight and normal-weight women for lower-body strength and overweight and normal-weight women for upper-body strength, especially for heavy objects throw variants. However, performance differences (assessed by ranks) are in most cases insignificant (Z values correspond to thresholds P>0.05). The only exceptions with significant differences (P<0.05) are for Overhead Medicine Ball Throw-forward (with the superiority of the overweight over the underweight) and Shot put - track and field (with the superiority of the overweight over the underweight). Conclusion: The constant involvement of female students in curricular and sports physical activities mitigates the differences between the muscle power of the 3 BMI categories. However, the small numerical composition - for the underweight and overweight groups - does not allow the generalization of the results, as studies on larger samples are needed and have common concerns related to the specifics of the sports practiced.